Testing the validity of purchasing power parity (PPP) in the newly industrialized countries (NICs) - Tan, Pei Yu (Universiti Malaysia Sarawak, (UNIMAS), 2010)
This study investigates the validity of purchasing power parity (PPP) Newly Industrialized Countries (NICs) using a univeriate unit root and ARDL approach. Quarterly data of 8 NICs (South Africa, Thailand, Tukey, the Philippines, Malaysia Brazil and India) are used to test for the long run PPP relationship with the China Yuan as base currency.